A Macroeconomic Determinants of Domestic Revenue Generation in Sierra Leone: A Fiscal Policy Perspective - Kamara, Ishmael; Gunawan, Indra; Hirawan, Fajar (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
This study examines the macroeconomic determinants of domestic revenue mobilization in Sierra Leone to propose effective strategies for enhancing public sector revenue. Using a conceptual framework, the study focuses on key independent variables such as real GDP, government expenditure, inflation, domestic debt, population growth, and the tax-to-GDP ratio. It analyses their influence on domestic revenue performance. The research adopts a quantitative ARDL methodology, utilizing time series data from 2001 to 2024 to identify long- and short-run relationships among the variables. The findings reveal a long-term relationship among the variables, while real GDP, inflation, population growth, and tax effort positively and significantly influence domestic revenue; government expenditure and domestic debt show a negative and significant long-term relationship. In the short run, however, lagged government expenditure and domestic debt appear to have a positive effect. These results suggest that short-term fiscal injections can boost revenue, but unsustainable expenditure and borrowing weaken long-term fiscal health. The study concludes that a balanced and transparent fiscal strategy anchored on growth-friendly policies, debt sustainability, and efficient public spending is essential for strengthening Sierra Leone’s domestic revenue capacity.